2005
DOI: 10.1111/j.1528-1167.2005.00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia in Children Treated with Antiepileptic Drugs Is Normalized by Folic Acid Supplementation

Abstract: Summary:Purpose: To assess the prevalence of hyperhomocysteinemia in pediatric patients treated with antiepileptic drugs (AEDs) and to evaluate the effect of folic acid supplementation on plasma total homocysteine (tHcy) concentrations in hyperhomocysteinemic patients.Methods: 123 patients from three regional hospitals participated in the study. Patients with hyperhomocysteinemia were included in a 3-month double-blind randomized trial testing oral folic acid supplementation (1 mg/day) versus placebo.Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
81
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(93 citation statements)
references
References 41 publications
7
81
0
5
Order By: Relevance
“…Moreover, the impact of genetic polymorphisms, vitamin concentrations and exogenous factors on tHcy in children has not yet been studied in detail. Since safe and cost effective strategies for prevention and treatment of hyperhomocysteinemia are well established (7,15), the present study is aimed at investigating tHcy, defining hyperhomocysteinemia and identifying factors influencing tHcy concentrations in a pediatric population. Therefore genetic polymorphisms, folate, Cbl, body mass index (BMI), blood pressure (BP), cholesterol, triglycerides, creatinine and lifestyle factors were investigated in a population of 264 young individuals.…”
mentioning
confidence: 99%
“…Moreover, the impact of genetic polymorphisms, vitamin concentrations and exogenous factors on tHcy in children has not yet been studied in detail. Since safe and cost effective strategies for prevention and treatment of hyperhomocysteinemia are well established (7,15), the present study is aimed at investigating tHcy, defining hyperhomocysteinemia and identifying factors influencing tHcy concentrations in a pediatric population. Therefore genetic polymorphisms, folate, Cbl, body mass index (BMI), blood pressure (BP), cholesterol, triglycerides, creatinine and lifestyle factors were investigated in a population of 264 young individuals.…”
mentioning
confidence: 99%
“…Die Einnahme der meisten klassischen Antiepileptika (Phenobarbital, Carbamazepin, Primidon, Valproat und Phenytoin) kann eine Hcy-Erhçhung auslçsen [135 -137], während dies nicht bei neueren Präparaten wie Lamotrigin oder Pergabalin beobachtet wurde [138]. Multimedikamentçse Behandlung und Langzeittherapie erhçhen das Risiko für HHcy [134]. Es gibt verschiedene Erklärungen für die Assoziation von HHcy mit antiepileptischen Pharmaka.…”
Section: Antiepileptikaunclassified
“…Der gestçrte Folat-Metabolismus erklärt wahrscheinlich die hç-here Rate an kongenitalen Mißbildungen bei Kindern von Müt-tern mit Antikonvulsivaeinnahme im ersten Trimester [144]. Eine orale Folsäure-Supplementation (1 mg/Tag) bei Kindern reduzierte erhçhte Hcy-Spiegel (> 10,4 ìmol/l) nach 6 bis 12 Wochen Behandlung signifikant [134]. Die Behandlung von Epileptikern mit Folatmangel mit 5 mg/Tag Folsäure über 1 -3 Jahre verbesserte deutlich die kognitiven Parameter, die Konzentrationsfähigkeit, die Stimmung und das Sozialverhalten [145].…”
Section: Antiepileptikaunclassified
“…AEDs are synergic with the C677T mutation in the methylenetetrahydrofolate reductase gene [48], but folate deficiency is promptly reversed by folate supplementation [49]. Other authors have reported myelodysplastic features in association with VPA [50].…”
Section: Review Of the Literaturementioning
confidence: 99%